Clinical effect of nighttime snacking on patients with hepatitis B cirrhosis - Han, Zuoqing; Li, Rongkuan; Zhong, Zhiwei; Piao, Yuetong; Guo, Rong (Frontiers in Nutrition, 2023)
Objective: Nighttime snacking is an effective intervention to avoid abnormal protein consumption caused by prolonged fasting. This article aims to evaluate the clinical efficacy of nighttime snacking on patients with hepatitis B cirrhosis and to provide new ideas for clinical nutritional intervention. Methods: The study participants were randomly assigned to the control group (n=30) and the observation group (n=30); the former was administered medical system treatment and routine dietary intervention, and the latter was administered the same treatment with the addition of nighttime snacking. After three months of intervention with different dietary guidance, the dry body weight body mass index (BMI), upper arm muscle circumference (AMC), grip strength, triceps skinfold thickness (TSF), third lumbar skeletal muscle index (L3-SMI), albumin (ALB), total bilirubin (T-BIL), cholinesterase (CHE), Fried’s frailty phenotype score, Child–Pugh score and various cirrhosis complication rates were compared between the two groups. Results: There was no significant difference in the baseline data between the two groups before the dietary intervention. After three months of regular dietary guidance in the control group, the grip strength increased compared with the baseline data (p<0.05), while the dry body weight BMI, AMC, TSF, L3-SMI, ALB, T-BIL, CHE, prothrombin time, international normalised ratio, prothrombin activity and Child–Pugh scores were not significantly different (p>0.05). After three months of dietary guidance with nighttime snacking in the observation group, the dry body weight BMI, grip strength, TSF, L3-SMI and CHE scores all increased, compared with the baseline data, while the Child–Pugh score decreased compared with the baseline level (all p＜0.05). After three months of intervention, the Child–Pugh score of the observation group showed a more significant decrease than the control group, while the dry body weight BMI, grip strength, ALB and CHE scores were all significantly higher than those in the control group (all p<0.05). Overall, the improvement rate was significantly higher in the observation group than in the control group (p<0.05). Conclusion: Nighttime snacking for hepatitis B cirrhosis patients with nutritional risk is beneficial in terms of the recovery of liver synthesis functions, improvements in clinical indicators, sarcopenia corrections and improvements in malnutrition-related complications.